Monitoring of microplastics in the clam Donax cuneatus and its habitat in Tuticorin coast of Gulf of Mannar (GoM), India. (November 2020) - Narmatha Sathish, M.; Immaculate Jeyasanta, K.; Patterson, Jamila
Abstract: Microplastics (MPs) in the marine environment are ubiquitous. The ingestion of these pollutants by marine organisms has drawn global attention. This work studies the distribution pattern and characteristics of MPs found in the body of the clam Donax cuneatus and its environment in order to understand the possible relationship between the MP concentration in the environment (water and sediment) and that in the clam's body. Samples of D. cuneatus were collected from the coast between Vembar and Periyathazhai in Tuticorin district along GoM. MP concentrations range from 0.6 to 1.3 items/g (wet weight) in clams, 10–30 items/l in water, and 24–235 items/kg in sediment. Small-sized clams contain the highest concentration of MPs. Hence it is hypothesised that allometric relationship exists between body size and MP concentration, depending on the surface-area to volume ratio. MP abundance in clam body has a clear, positive, significant correlation with MP abundance in sediment but not with abundance of MP in water. Microplastics of fiber type with size 100–250 μm have a predominant presence in clams. The study identified ten types of polymers, of which polyethylene is the most common polymer in all sample types. FTIR-ATR spectra and surface morphology indicate that most of the microplastics have been strongly weathered. Energy dispersive X-ray spectroscopy analysis detected heavy metals associated with MPs like Cd, Pb, Cu, Zn, Ni and Fe. Filter-feeding clams like Donax sp. can provide valuable information on the spatial patterns of MP distribution, and so can act as bio-indicators in monitoring MP pollution in coastal areas. Graphical abstract: Image 1 Highlights: 100–250 μm range, PE fibers were the most common MPs in clam. MPs abundance decreases with increasing size of clam. MP distributions in clam closely reflected those in sediment. Sediments contained a broader range of MPs than seawater. Abstract : This study describes the abundance, characteristics and morphology of MPs in the clam ( Donax cuneatus ) and its habitat.